Gaze behaviour and vocal feedback in task-based dyadic conversations with and without eye contact - Sbranna, Simona; Savino, Michelina; Baills, Florence; Grice, Martine (Frontiers in Communication, 2025)
Human communication is multimodal, with verbal and non-verbal cues such as eye gaze and vocal feedback being crucial for managing interactions. While much research has focused on eye gaze and turn alternation, few studies explore its relationship with turn-regulating vocal feedback. This study investigates this interplay during a Tangram game in Italian under two visibility conditions: face-to-face and separated by a screen. The results show that feedback producers rarely look at receivers, while receivers more frequently look at producers, suggesting that they might be eliciting vocal feedback. Without visual contact, gaze shifts decrease and vocal feedback increases. Interestingly, when visual contact is absent, gaze directed towards where the addressee is sitting does not coincide with vocal feedback, raising questions about what prompts this gaze.